2019
DOI: 10.1007/s00408-019-00262-z
|View full text |Cite
|
Sign up to set email alerts
|

Electronic Cigarette Advertising Impacts Adversely on Smoking Behaviour Within a London Student Cohort: A Cross-Sectional Structured Survey

Abstract: IntroductionIn contrast to tobacco smoking, electronic cigarette (“vaping”) advertisement had been approved in the United Kingdom (UK) in January 2013. Currently, there are an estimated 3.2 million UK e-cigarette users. The impact of e-cigarette advertisement on tobacco use has not been studied in detail. We hypothesised that e-cigarette advertisement impacts on conventional smoking behaviour.MethodsA cross-sectional structured survey assessed the impact of e-cigarette advertising on the perceived social accep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 43 publications
1
4
0
Order By: Relevance
“…In a separate model that included the number of channels through which participants were exposed to e-cigarette advertisements (Table 3), participants who noticed advertisements in more places were more likely to perceive e-cigarettes of the acceptability of their use. This finding is consistent with a study in a cohort of university students (20-24 years) in the United Kingdom of Great Britain and Northern Ireland which found that exposure to e-cigarette advertisements increased the social acceptability of both e-cigarette use and smoking (14). Previous research has shown that e-cigarette advertisements as lifestyle marketing tend to be more effective when the advertisements feature characters who are similar to a person's peers (15), and such advertising could increase how socially acceptable or desirable these devices are, thus increasing their use or even functioning as a gateway to smoking initiation (16,17).…”
Section: Table 2 Perception Of Smokers and E-cigarette Users About Th...supporting
confidence: 91%
“…In a separate model that included the number of channels through which participants were exposed to e-cigarette advertisements (Table 3), participants who noticed advertisements in more places were more likely to perceive e-cigarettes of the acceptability of their use. This finding is consistent with a study in a cohort of university students (20-24 years) in the United Kingdom of Great Britain and Northern Ireland which found that exposure to e-cigarette advertisements increased the social acceptability of both e-cigarette use and smoking (14). Previous research has shown that e-cigarette advertisements as lifestyle marketing tend to be more effective when the advertisements feature characters who are similar to a person's peers (15), and such advertising could increase how socially acceptable or desirable these devices are, thus increasing their use or even functioning as a gateway to smoking initiation (16,17).…”
Section: Table 2 Perception Of Smokers and E-cigarette Users About Th...supporting
confidence: 91%
“…Exposure to e-cigarette marketing and advertising has increased among youth in recent years [11] and prior research suggests such exposure may be associated with perceptions of, interest in, and use of e-cigarettes among youth and young adults . The majority of previous studies on e-cigarette advertising utilized either a cross-sectional [12][13][14][15][16][17][18][19][20]33,36,39,40] or experimental design [21][22][23][24][25][26] to assess associations between advertising and e-cigarette perceptions, susceptibility, or use. Among the cross-sectional studies, many utilized National Youth Tobacco Survey (NYTS) data on reported advertising exposure via several media channels and e-cigarette use, or intentions to use [12,[14][15][16][17][18][19]39].…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, much of the prior e-cigarette advertising research involves only youth aged 11-17 years [12][13][14][15][16][17][18][19][21][22][23][24][25][28][29][30]32,33,[38][39][40], with few examining the impact of ecigarette advertising specifically on young adults aged 18-29 years [20,26,31,35,37]. Chen-Sankey et al examined a cohort of both youth and young adults to assess the impact of advertising exposure on e-cigarette use, finding a relationship between marketing exposure and e-cigarette experimentation [27].…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that e-cigarette aerosols contain nicotine, carbonyl compounds, nitrosamines, lead, cadmium and other harmful substances 5 , 6 , but the content of these harmful substances is significantly lower than that of tobacco 7 . The industry has adopted active marketing strategies on media and social networks to promote e-cigarettes as a healthier alternative to cigarettes 8 , 9 . However, harm reduction does not mean ‘no risk’.…”
Section: Introductionmentioning
confidence: 99%